METAPHORICAL PERCEPTIONS OF UNIVERSITY STUDENTS REGARDING THE CONCEPT OF “LEADER” (Third Sector Social Economic Review, 2022)
This study aims to reveal university students' perceptions of the concept of the leader through metaphors. The research model is in the phenomenology model, which is one of the qualitative research models. The population of the research consists of actively registered students at Tokat Gaziosmanpasa University in the 2020-2021 academic years. There are a total of 30.851 students (associate degree, bachelor's degree, master’s degree, and Ph.D.) in the state university in this academic year. A questionnaire form was applied to reveal the mental images of 756 students who accepted to participate in the study regarding the concept of the leader. In the coding and sequencing phase of the research, it was examined whether the metaphors associated with the concept of the leader were clear, but 170 students' papers were deemed invalid (no metaphor, weak metaphor imagery, logical basis), and the analysis of the research data was made with metaphors obtained from 586 students. 10 different main themes (authoritarian, guiding, fair, protective, wisdom, life source, peak, natural power, connective, and hardworking) were created in the metaphorical perceptions of the students regarding the concept of leader.
Keywords: leader; leadership; metaphor; university student.